Association between Malnutrition Inflammation Score and Latent Tuberculosis among Chronic Hemodialysis Patients - Ria Bandiara; Lilik Sukesi; Astried Indrasari; Alif Bagus Rakhimullah; Afiatin Afiatin; Prayudi Santoso (Faculty of Medicine Universitas Padjadjaran, 2021)
Objective: To investigate the association of malnutrition with latent tuberculosis (TB) among chronic kidney disease (CKD) patients on hemodialysis (HD).Methods: This was a cross-sectional study conducted at the Hemodiaylisis Unit of Dr. Hasan Sadikin General Hospital, Bandung, Indonesia. Subjects were patients aged >18 years who had undergone HD twice a week for at least three months. Patients suspected of active tuberculosis (TB), malignancy, or immunocompromised were excluded. Latent TB was diagnosed using the interferon-gamma release assays (IGRA). Malnutrition was defined by a malnutrition inflammation score (MIS) of less than 5. All data including age, sex, CKD etiologies, and laboratory findings were obtained and recorded in a case report form.Results: A total of 120 subjects were involved in this study. Subjects with positive, negative, and indeterminate IGRA results were 39.2%, 56.7%, and 4.2%, respectively. There was no significant differences in subjects characteristics between positive and negative IGRA subjects. The MIS>5 was shown to have no statistically significant association with positive IGRA subjects (OR=3.47, 95%CI 0.93–12.93).Conclusion: Malnutrition based on an MIS score of less than 5 is not statically associated, but clinically associated, with latent TB. Further causal inference study to investigate these associations is needed.